(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
There is a set of economic factors that affect the rationalization of decisions on unexploited resources within the economic unit and here determines the problem of the search for the question of what economic factors cause the emergence of asymmetric costs, and aims to identify these factors in the costs of adjustment to resources, change in The size of the activity of the economic unit, the general trend of sales change in the previous period, and the economic level of the country. Rh measure the impact of these factors on economic unity, and taking into consideration the impact when formulating decisions.